Okara or soybean grain added to the rehydrated corn grain silage for cattle: digestibility, degradability and ruminal parameters - Tres, Tamara Tais (2020)
The experiment was carried out to evaluate total and partial digestibility of nutrients, the efficiency of microbial protein synthesis, in situ degradability and ruminal parameters in cattle fed diets with rehydrated corn grain silages, okara or soybean grain. Three Holstein steers were distributed in a 3 x 3 Latin square design. The treatments evaluated were: SO (corn grain silage + 30% okara), SSG (corn grain silage + 20% soybean grain) and CG (dry corn grains). The ruminal digestibility of non-fiber carbohydrates (NFC) increased in SO (88.34%) and SSG treatments (87.87%), compared to the CG treatment (63.48%). The minimum ruminal pH value was 6.01, observed 4.13 hours after feeding a diet with SO. The highest ammonia-N contents were 15.25 and 15.07 mg dL-1 observed in SSG and SO, respectively, 2.45 and 2.61 hours after feeding. Treatments SO and SSG showed higher fraction A content (readily degradable fraction) and C (constant rate of degradability of fraction B). The effective degradability (ED) of dry matter (DM) was higher for the diets SO and DE of CP was higher for treatments SO and SSG. SSG and SO result in better utilization of nutrients by animals.